Niña Kayapo - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a una niña de la etnia Kayapo lista para celebrar la fiesta a demas de tener el pelo rapado el cuerpo pintado tambien lleva atravesado o puesto hilos de algodon teñido de color rojo que representa la virginidad de la niña que no esta preparado para la vida sexual.
ENGLISH: A girl from the Kayapo ethnic group was observed ready to celebrate the party. In addition to having shaved hair, her painted body also has red dyed cotton threads crossed or worn, which represents the virginity of the girl who is not prepared for life. sexual.

SPANISH: Se observó a una niña de la etnia Kayapo lista para celebrar la fiesta a demas de tener el pelo rapado el cuerpo pintado tambien lleva atravesado o puesto hilos de algodon teñido de color rojo que representa la virginidad de la niña que no esta preparado para la vida sexual.
ENGLISH: A girl from the Kayapo ethnic group was observed ready to celebrate the party. In addition to having shaved hair, her painted body also has red dyed cotton threads crossed or worn, which represents the virginity of the girl who is not prepared for life. sexual.
Kayapo girl
Keywords: Mato Grosso (Brazil)--Indigenous Community|~|Brazil--Indigenous populations|~|Mato Grosso (Brasil)|~|Comunidad Indigena|~|Brasil|~|Poblaciones Indigenas|~|Mato Grosso (Brazil)|~|Indigenous Community|~|Brazil|~|Indigenous Populations